1997
DOI: 10.1017/s1355770x97000132
|View full text |Cite
|
Sign up to set email alerts
|

Soil degradation and economic development in Ghana

Abstract: Soil erosion and soil mining are important environmental problems in many developing countries and may represent a considerable drag on economic development. The cost of soil degradation depends, however, not only on the productivity effects it has on agricultural growth, but also on how the agricultural sectors are linked to the rest of the economy. This article describes an integrated economy–soil-productivity model for Ghana, and through several simulated scenarios we calculate the drag on the Ghanaian econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…In this study, although the SOC stock was significantly different between the two depths within each stand, the value did not vary significantly between the stands. Bulk density can be a useful indicator of soil changes which can be attributed to losses in soil quality, soil aggregation resulting in a loss of the superficial layers, creating compaction and erosion process problems, increasing the loss of physical and chemical soil quality (Alfsen et al 2001;Jaramillo et al 2004;Loaiza Usuga et al 2010). In the present study, soil depth-specific bulk density did not change in the stands.…”
Section: Discussionmentioning
confidence: 40%
“…In this study, although the SOC stock was significantly different between the two depths within each stand, the value did not vary significantly between the stands. Bulk density can be a useful indicator of soil changes which can be attributed to losses in soil quality, soil aggregation resulting in a loss of the superficial layers, creating compaction and erosion process problems, increasing the loss of physical and chemical soil quality (Alfsen et al 2001;Jaramillo et al 2004;Loaiza Usuga et al 2010). In the present study, soil depth-specific bulk density did not change in the stands.…”
Section: Discussionmentioning
confidence: 40%
“…This suggests that any policy that influences output price will have more or less a similar impact on the long run behavior of an indebted rural smallholder as on a household that is debt free. The policy conclusions emerging from more general models of household resource management strategies that analyze output price changes may be valid for both debt free and chronically indebted rural smallholders (see, for example, Alfsen et al 1997;Anderson and Thampapillai 1990;Barbier 1990 and1998;Barbier and Burgess 1992b;Coxhead and Jayauriya 1994;Freeman et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…For example, a considerable empirical literature now exists on the impacts of agricultural input and output price changes on the incentives for rural households in developing countries to conserve or degrade their land holdings (see, for example, Alfsen et al 1997;Anderson and Thampapillai 1990;Barbier 1990 and1998;Barbier and Burgess 1992b;Coxhead and Jayauriya 1994;Freeman et al 1997). Most reviews of this literature have concluded that the impacts of price changes on farmers' incentives to degrade their land will be influenced by a variety of economic factors, but generally an increase in aggregate input or output prices will not affect these incentives as much as changes in relative prices that influence the returns to less erosive, compared to more erosive, cropping systems (Anderson and Thampapillai 1990;Barbier 1998;Barbier and Burgess 1992a).…”
Section: The Effects Of Policy Changesmentioning
confidence: 99%
“…Such two-way linkages between ecology and economy in macroeconomic models have, to some degree, been applied in models where economic activity causes pollution, entailing corrosion on real capital and sick-leaves with a negative impact on economic production. Alfsen et al (1997) and Grepperud and Wiig (1999) have made similar ecology-economy linkages through agricultural production in CGE models. The technical contribution of this study is the inclusion of the soil degradation model in the production functions as a time-dependent Hicks' neutral productivity coefficient.…”
Section: Introductionmentioning
confidence: 93%
“…Barbier (1998) included the EPIC in an economic setting for a village in Burkina Faso in order to describe the optimal migration pattern. Alfsen et al (1997) measured the implication of greater openness on migration to the rain forests of Ghana, while Grepperud and Wiig (1999) assess the effect of staple food exports on the GDP for Tanzania.…”
Section: Introductionmentioning
confidence: 99%